Prospective evaluation of the Sunshine Appendicitis Grading System score. Issue 5 (1st September 2015) - Reid, Fiona; Choi, Julian; Williams, Marli; Chan, Steven
Abstract: Background: Although there is a wealth of information predicting risk of post‐operative intra‐abdominal collection and guiding antibiotic therapy following appendicectomy, confusion remains because of lack of consensus on the clinical severity and definition of 'complicated' appendicitis. This study aimed to develop a standardized intra‐operative grading system: Sunshine Appendicitis Grading System (SAGS) for acute appendicitis that correlates independently with the risk of intra‐abdominal collections. Methods: Two‐hundred and forty‐six patients undergoing emergency laparoscopy for suspected appendicitis were prospectively scored according to the severity of appendicitis and followed up for complications including intra‐abdominal collection. After termination of the study, the SAGS score was repeated by an independent surgeon based on operation notes and intra‐operative photography to determine inter‐rater agreement. The primary outcome measure was incidence of intra‐abdominal collection, secondary outcome measures were all complications and length of stay. Results: SAGS score demonstrated good inter‐rater agreement (kappa Kw 0.869; 95% CI 0.796–0.941; P < 0.001). A risk ratio of 2.594 (95% CI 0.655−4.065; P < 0.001) for intra‐abdominal collection was found using SAGS score as a predictor. The discriminative ability of SAGS score was supported by an area under the curve value of 0.850 (95% CI 0.799–0.892; P < 0.001). Conclusions: SAGS score can be used to simply and accurately classify the severity of appendicitis and to independently predict the risk of intra‐abdominal collection. It can therefore be used to stratify risk, guide antibiotic therapy, follow‐up and standardize the definitions of appendicitis severity for future research.